Effect of bioflavonoid quercetin on the course of inflammatory process in herpetic keratitis patients with dry eye syndrome - S. Ya. Rafalyuk (Journal of Ophthalmology, 2016)
Backup: The problem of dry eye syndrome is of great importance and significance in ophthalmology.